Recombinant human activated protein C in sepsis: previous concerns and current usage. Issue 1 (1st September 2004) - Haley, Michael; Cui, Xizhong; Minneci, Peter C; Deans, Katherine J; Natanson, Charles; Eichacker, Peter Q
Recombinant human activated protein C (rhAPC) was approved by the FDA for clinical use in severely septic patients approximately 2 years ago. This approval, based upon the results of the Phase III clinical trial, Phase III Protein C Worldwide Evaluation in Severe Sepsis (PROWESS), was not without opposition as concerns regarding rhAPC's inconsistent effects during the trial, incomplete understanding of its mechanism of action, and its safety profile within various subgroups were questioned during the FDA's evaluation. In light of these concerns, we have attempted to assess rhAPC's cost effectiveness by first comparing its performance in recent clinical use to that of the Phase III trial and then by examining other potentially less expensive treatments with effects that may overlap with rhAPC. Recent postmarketing analysis suggests a higher mortality rate in patients with similar disease severity (number of injured organs) during the clinical use of rhAPC when compared with the Phase III trial. Furthermore, the clinical use of rhAPC may also be associated with a higher incidence of bleeding risk or other adverse events that necessitate the discontinuation of treatment with rhAPC. A recent meta-analysis and other Phase III trials assessing agents with antithrombotic or anti-inflammatory properties, suggest that both heparin and physiologic-dose steroids may offer less expensive alternatives to rhAPC. The results of recently completed and ongoing Phase IV trials will be helpful in defining rhAPC's role in the treatment of sepsis.